Specificity of the Double-Stranded RNA-Binding Domain from the RNA-Activated Protein Kinase PKR for Double-Stranded RNA: Insights from Thermodynamics and Small-Angle X‑ray Scattering - Patel, Sunita (2012)
The interferon-inducible, double-stranded (ds)RNA-activated protein kinase (PKR) contains a dsRNA-binding domain (dsRBD) and plays key roles in viral pathogenesis and innate immunity. Activation of PKR is typically mediated by long dsRNA, and regulation of PKR is disfavored by most RNA imperfections, including bulges and internal loops. Herein, we combine isothermal titration calorimetry (ITC), electrophoretic mobility shift assays (EMSAs), and small angle X-ray scattering (SAXS) to dissect the thermodynamic basis for specificity of the dsRBD termed ‘p20’ for various RNAs, and to detect any RNA conformational changes induced upon protein binding. We monitor binding of p20 to chimeric duplexes containing terminal RNA-DNA hybrid segments and a central dsRNA segment, which was either unbulged (‘perfect’) or bulged. The ITC data reveal strong binding of p20 to the perfect duplex (K(d)~30 nM) and weaker binding to the bulged duplex (K(d)~2-5 μM). SAXS reconstructions and p(r) distance distribution functions further uncover that p20 induces no significant conformational change of perfect dsRNA but largely straightens bulged dsRNA. These observations support the dsRBD’s ability to tightly bind only to A-form RNA and suggest that in a non-infected cell, PKR may be buffered via weak interactions with various bulged and looped RNAs, which it may straighten. This work suggests that PKR-regulating RNAs having complex secondary and tertiary structures likely mimic dsRNA and/or engage portions of PKR outside of the dsRBD.